MOTIVATION OF BORNEO TARAKAN UNIVERSITY STUDENTS IN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Rianto, Agus (Borneo Journal of English Language Education, 2019)
This study aims to analyze the motivation level of Borneo Tarakan University students in learning English as a foreign language. Respondents surveyed in this study amounted to 265 people consisting of 189 female and 76 male students. The instrument used was a questionnaire adopted from the Attitude/Motivation Test Battery (AMTB) developed by Gardner. The results of the study showed that in general the students of Boneo Tarakan University had a high level of motivation in learning English. According to them learning English was important both for integrative and instrumental oriented purposes. There were significant differences between male and female students in the mean scores of integrative motivation and instrumental motivation. However, by English achievement, significant difference was not found in the mean scores of integrative motivation and instrumental motivation.